The Language of Violence The Written Press, The Parties and the Church. Medellin, 1950 (2004)
This paper presents the characteristics of violence that the city of Medellín experienced in the fifties. It shows how the political parties, The Church, and the Printing Press were mediators of the violence in the city. The article illustrates the way in